A magnetic resonance imaging study on the temporomandibular joint disc–condyle relationship in young asymptomatic adults. Issue 2 (February 2022) - Luo, D.; Yang, Z.; Qiu, C.; Jiang, Y.; Zhou, R.; Yang, J.
Abstract: The aim of this study was to assess the temporomandibular joint (TMJ) disc–condyle relationship in asymptomatic young adults. Ninety-three volunteers aged 19–23 years without temporomandibular disorder (TMD) symptoms underwent TMJ magnetic resonance imaging (MRI). The condylar centre and apex methods were used to measure and analyse the position of the disc in the oblique sagittal plane, and the reliability of the two methods was compared by calculating the intra-class correlation coefficient (ICC). Furthermore, 18 of the volunteers were randomly selected for three-dimensional (3D) reconstruction of the TMJ structure and the disc–condyle relationship. The 3D TMJ structure was established by semi-automatic segmentation of the condyle and articular disc in ITK-SNAP software; the condylar apex method was then performed. It was found that only 33.3% of the posterior edge of the articular discs were located in the normal 12 o'clock position with respect to the condyle. Moreover, this study suggests that the condylar centre method lacks accuracy when compared to the condylar apex method in regard to the measurement of the TMJ disc–condyle relationship (0 < ICCcen < ICCapex < 1). The position of the articular disc (left and right) was more forward in young women when compared to young men. However, there was no significant difference in the TMJ disc–condyle position between the left and right sides in the same individual, although the two joint discs in the same individual were not completely symmetrical.